Pyrolysis of Algal Biomass Obtained from High-Rate Algae Ponds Applied to Wastewater Treatment - Vargas e Silva, Fernanda; Monteggia, Luiz Olinto (Frontiers in Energy Research, 2015)
This work presents the results of the pyrolysis of algal biomass obtained from high-rate algae ponds treating sewage. The two high-rate algae ponds (HRAP) were built and operated at the São João Navegantes Wastewater Treatment Plant. The HRAP A was fed with raw sewage while the HRAP B was fed with effluent from an upflow anaerobic sludge blanket (UASB) reactor. The HRAP B provided higher productivity, presenting total solids concentration of 487.3 mg/l and chlorophyll a of 7735 mg/l. The algal productivity in the average depth was measured at 41.8 g·m−2 day−1 in pond A and at 47.1 g·m−2 day−1 in pond B. Algae obtained from the HRAP B were separated by the process of coagulation/flocculation and sedimentation. In the presence of alum, a separation efficiency in the range of 97% solid removal was obtained. After centrifugation the biomass was dried and comminuted. The biofuel production experiments were conducted via pyrolysis in a tubular quartz glass reactor which was inserted in a furnace for external heating. The tests were carried out in an inert nitrogen atmosphere at a flow rate of 60 ml/min. The system was operated at 400, 500, and 600°C in order to determine the influence of temperature on the obtained fractional yields. The studies showed that the pyrolysis product yield was influenced by temperature, with a maximum liquid phase (bio-oil and water) production rate of 44% at 500°C, 45% for char and around 11% for gas.